DETERMINANT FACTORS THAT INFLUENCE THE ORIGINAL INCOME OF THE VILLAGE - Farida Rika Arini; Icih Icih; Trisandi Eka Putri (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2021)
This study aims to determine the factors that influence the original income of the village. The objects in this study are villages in the Subang Districts area. This research is a quantitative study using secondary data types. The sample selection technique uses purposive sampling to produce 103 villages. The results showed that: (1) Village financial management partially has a significant positive effect on village original income, (2) Village building index partially has no effect on the original income of the village, (3) education level of the apparatus of the village government partially did not have effect on village original income, (4) Village consultative bodies partially do not affect the village's original income, (5) village financial management, village building index, education level of the apparatus of the village government and village consultative bodies simultaneously have a significant effect on village original income.